Supported multi-metal cyanide complex catalyst as well as preparation method and application thereof
By loading the polymetallic cyanide complex catalyst on the MCM-41 (OH-) support and combining Igepal CA-520 as a co-complexing agent, a nano-scale catalyst is formed, which solves the problems of long induction period and many by-products in traditional polymerization methods, and achieves efficient and safe synthesis of polymer polypropylene glycol.
Patent Information
- Application Number
- CN202411902353.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
AI Technical Summary
When synthesising propylene oxide polyether polyols, traditional anion polymerization methods have problems such as long induction period, many by-products, difficult to separate the catalyst from the product, high reaction temperature and high risk.
A supported polymetal cyanide complex catalyst was used to form a nanoscale catalyst to improve catalytic activity and selectivity by supporting Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn3[Ni(CN)4] on the MCM-41(OH-) support.
It has achieved high catalytic activity, low loss of active ingredients, short induction period, and few by-products. In the external circulation kettle reactor, the continuous synthesis of polymer polypropylene glycol is realized, improving production safety and product quality.
Smart Images

Figure BDA0005203534450000071 
Figure BDA0005203534450000081 
Figure BDA0005203534450000082
Abstract
Description
Technical Field
[0001] The invention relates to a heterogeneous catalyst and a preparation method and application thereof, and in particular to a supported multi-metal cyanide complex catalyst and a preparation method and application thereof. Background Art
[0002] Polyether polyols are a class of polymer compounds with ether bonds (ROR) and terminal hydroxyl groups (OH groups). They are prepared by using low molecular weight compounds (such as alcohols and amines) as initiators and reacting with compounds containing epoxy structures to form a ring-opening polymerization reaction. This synthetic material has a wide range of applications in multiple industrial fields, including the preparation of polyurethanes, surfactants, and water-based functional liquids.
[0003] To date, industrial-scale ring-opening polymerization of alkylene oxides mainly uses alkali metal hydroxides as anionic polymerization catalysts, among which potassium hydroxide is the most commonly used catalyst. However, there are some problems in the traditional anionic polymerization method for synthesizing propylene oxide polyether polyols. The first problem is that under strong alkaline conditions, propylene oxide monomers undergo isomerization to generate allyl alcohol anions, which participate in the reaction as new initiation points and chain growth points, resulting in a widening of the product molecular weight distribution width, a decrease in reaction selectivity, and a limitation on the growth of molecular weight; the second problem is that homogeneous base catalysis will lead to a complex product post-processing process, resulting in environmental pollution and equipment corrosion, and increasing production costs.
[0004] At present, the most widely used catalyst for the preparation of polyether polyols in industry is the double metal cyanide complex catalyst (DMC), but it mainly faces the following problems: (1) the reaction induction period is long; (2) the polypropylene glycol product prepared by the existing zinc-cobalt bimetallic catalyst contains some by-product propylene ester, and the selectivity needs to be improved; (3) the catalyst and the product cannot be separated, resulting in a large amount of metal residue in the product, affecting the performance; (4) the reaction temperature is high and the reaction is exothermic, which is very dangerous when operated in a kettle reactor and cannot be produced continuously.
[0005] Multi-metal cyanide complex catalyst (MMC) is a highly efficient catalyst for epoxide polymerization. Compared with traditional catalysts such as acids and bases, the catalytic effect of MMC is improved, but the catalytic performance still needs to be further improved and the induction period still needs to be shortened. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a supported multi-metal cyanide complex catalyst with high catalytic activity, low loss of active ingredients and short induction period;
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned supported multi-metal cyanide complex catalyst;
[0008] The third object of the present invention is to provide the use of the above-mentioned supported multi-metal cyanide complex catalyst.
[0009] Technical solution: The supported multi-metal cyanide complex catalyst of the present invention satisfies the following general formula:
[0010] Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn[Ni(CN)4]@MCM-41(OH-)·vZnCl2·xLa(NO3)3·y t BuOH·z Igepal CA-520, wherein MCM-41(OH-) represents an alkali-treated mesoporous molecular sieve; v=0.5-3, x=0-0.01, y=0.1-2, z=0-0.1.
[0011] The preparation method of the above-mentioned supported multi-metal cyanide complex catalyst comprises the following steps:
[0012] (1) calcining MCM-41 powder and mixing it with alkali solution, stirring, cooling to room temperature, washing, drying, and grinding the product into powder; adding the powder into an ion exchange solution for ion exchange, washing, filtering, and drying to obtain an alkali-treated MCM-41 carrier, which is recorded as MCM-41(OH-);
[0013] (2) Dissolve three metal cyanides, K3[Co(CN)6], K3[Fe(CN)6] and K2[Ni(CN)4], respectively, and the resulting solutions are named solution A, solution B and solution C, respectively; disperse MCM-41(OH-) in a solvent to obtain an MCM-41(OH-) solution, and then add ZnCl2, La(NO3)3, t BuOH and Igepal CA-520, and the resulting solution was named solution D;
[0014] (3) adding solution A, solution B and solution C dropwise into solution D, stirring to obtain catalyst slurry; filtering, washing and drying the catalyst slurry to obtain the supported multi-metal cyanide complex catalyst.
[0015] Wherein, in step (1), the MCM-41 molecular sieve carrier is calcined in an air atmosphere at a temperature of 450-650°C for 4-6 hours. The concentration of the alkaline solution is 0.05-0.3 mol / L, and the alkali is preferably NaOH; the solid-liquid ratio (g / mL) of MCM-41 to the alkaline solution is 1:10-20; the concentration of the ion exchange solution is 0.3-0.7 mol / L, and the ion exchange solution is preferably NH4Cl solution; the solid-liquid ratio (g / mL) of the powder to the ion exchange solution is 1:10-20.
[0016] Wherein, in step (2), the concentration of K3[Co(CN)6] solution is 0.05-0.5 g / ml, and the concentrations of K3[Fe(CN)6] and K2[Ni(CN)4] solutions are 5-20% of the concentration of K3[Co(CN)6] solution, respectively.
[0017] Wherein, in step (2), the t The mass ratio of BuOH to MCM-41(OH-) solution is 1:1-2, the mass ratio of ZnCl2 to MCM-41(OH-) is 5-1:1, and the mass ratio of the sum of the masses of the three metal cyanides to MCM-41(OH-) is 2-1:1. The concentration of the MCM-41(OH-) solution is 0.01-0.1 g / ml, and MCM-41(OH-) is preferably dispersed in deionized water.
[0018] Wherein, in step (2), the mass ratio of La(NO3)3 to MCM-41(OH-) is 1:5-20; the mass ratio of Igepal CA-520 to MCM-41(OH-) is 2-1:1.
[0019] Wherein, in step (3), the dropping time is 10-30 min, and stirring is continued for 30-90 min at a stirring rate of 2500-3500 rpm and a temperature of 30-60° C. to obtain a catalyst slurry.
[0020] Wherein, in step (3), the filter cake obtained by filtration needs to be washed with an aqueous solution of an organic ligand at least three times, and the volume ratio of the organic ligand to deionized water is gradually increased; and the drying temperature of the obtained filter cake is 50-80°C.
[0021] The use of the above-mentioned supported multi-metal cyanide complex catalyst in the preparation of high molecular weight polypropylene glycol.
[0022] The reaction temperature is 100-140°C, the pressure is 0.1-0.5MPa, the feed ratio is 8:12-72, specifically 8g:12-72g; and the single input amount is 1-12g.
[0023] Among them, the device used for synthesizing high molecular weight polypropylene glycol is an external circulation kettle reactor; the external circulation kettle reactor includes a reactor body, an air intake system, and an external circulation system; a stirring device and a heating device for heating the reactor are arranged in the reactor body, and the stirring device and the heating device are respectively connected to the high pressure kettle controller; the air intake system is connected to the reactor body for conveying raw material gas and protective gas to the reactor body; the external circulation system includes a plunger pump, and the plunger pump is respectively connected to the external circulation outlet at the lower part of the reactor body and the external circulation inlet at the upper part of the reactor body through pipelines.
[0024] Principle of the invention:
[0025] (1) Smaller catalyst size and crystallinity are conducive to improving catalyst performance. The general formula of the multimetal cyanide complex, i.e., nanoporous Prussian blue analogue, is M a 2+ [M b 3+ (CN) c ] d , composed of the octahedral structure M b 3+ (CN) c By M a 2+ ion bridges, thus forming a cubic lattice. This cubic lattice is composed of alternating M a 2+ and M b 3+ ions form crystals, linked together by cyanide linkages, forming "defect-free" pores without any unsaturated metal centers. a 2+ With M b 3+ (CN) c The charge imbalance between the structures leads to 1 / 3 of the M b 3+ Disordered M at the site b 3+ (CN) c Vacancies maintain the electrical neutrality of the crystal structure, and these vacancies provide space for the subsequent introduction of metal ions. Therefore, in the structure of zinc-cobalt double metal cyanide, Zn3[Co(CN)6]2, Zn 2+ The charge balance of the ions results in one-third of the [Co(CN)6] 3 - site becomes vacant, where a new ligand [Fe(CN)6] can be introduced 3 - and [Ni(CN)6] 3 -, forming Zn3[Fe(CN)6]2 and Zn3[Ni(CN)6]2 structures. The active center of the polymerization of multi-metal cyanide complex catalyst (MMC) is the chelated metal Zn 2+The synergistic effect of multiple metal cyanide components increases the content of amorphous components in the catalyst. In addition, Zn3[Fe(CN)6]2 and Zn3[Ni(CN)6]2 have larger specific surface areas and more active sites. Therefore, multi-metal cyanide complex catalysts (MMC) show higher catalytic activity than ordinary double metal cyanide catalysts (DMC). The electronegativity of zinc decreases with the increase of coordination number. Because of the introduction of metal Ni(Ⅱ) and Fe(Ⅲ), the coordination amount of zinc increases, the electronic contribution value of cyanide ligands to zinc decreases, the coordination strength between the central atom zinc and the ligand decreases, and the crystallinity of the catalyst is also smaller. Therefore, the introduction of metal Ni(Ⅱ) and Fe(Ⅲ) can increase the specific surface area of the catalyst, provide more active sites, and reduce the crystallinity of the catalyst, thereby improving the activity and selectivity of the catalyst.
[0026] (2) Water molecules are Zn 2+ The resulting cavity can be filled with bound and dissolved forms, and the organic ligand can bind to the Zn 2+ After replacing the bound water molecules, the organic ligands generate open coordination sites and interact with each other to form active catalysts. t BuOH. In the presence of a co-complexing agent, MMC can generate nano-sized MMC through a reverse emulsification reaction. Igepal CA-520 is a nonionic surfactant that assists in emulsification and disperses the oil-water interface, thereby promoting the reaction. Igepal CA-520 can react with ZnCl2, Zn3[Co(CN)6] 2、 Zn[Ni(CN)4] and Zn3[Fe(CN)6]2 react to coordinate the oxygen atoms in the co-complexing agent Igepal CA-520 with Zn to form new active centers. At the same time, the co-complexing agent Igepal CA-520 can control the size of MMC particles and synthesize MMC in the particle size range of 50-100nm. Smaller MMC particle size is beneficial to the loading on the MCM-41(OH-) carrier and the improvement of catalyst performance.
[0027] (3) Since the amount of MMC catalyst used is small, it is difficult to extract the catalyst remaining in the product by conventional filtration methods. Therefore, MMC with active ingredients is loaded on the MCM-41 (OH-) carrier to achieve a simple separation of the catalyst and the product while ensuring that the catalyst is in full contact with the reactants. This not only avoids residual metals in the product, but also achieves the regeneration and reuse of the catalyst.
[0028] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0029] (1) Based on the traditional zinc-cobalt double metal cyanide catalyst (DMC), metal Ni (II) and Fe (III) were introduced to prepare a multimetal cyanide complex catalyst (MMC), which reduced the crystallinity of the catalyst, increased the specific surface area of the catalyst, improved the catalytic activity of the catalyst, shortened the reaction induction period, and reduced the number of by-products; (2) The co-complexing agent Igepal was added during the preparation of MMC. CA-520, reduces the particle size of the catalyst and increases the number of active sites of the catalyst; (3) The MMC catalyst is loaded on the MCM-41 (OH-) carrier, which is easy to separate from the product, the active ingredients are not easy to lose, and the catalyst life is long; (4) The obtained high molecular weight polypropylene glycol product has a narrow molecular weight distribution width and a low aldehyde value, and has broad application prospects; (5) The use of heterogeneous catalysts in an external circulation kettle reactor to continuously synthesize high molecular weight polypropylene glycol is realized, and the mixing between reactants and products is promoted by external circulation, thereby accelerating the reaction rate; the reaction heat generated during polymerization is removed in time by external circulation, avoiding the "violent polymerization" phenomenon caused by excessive local temperature in the kettle, improving the product color and improving production safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a SEM image of the catalyst prepared in Example 1;
[0031] Figure 2 TG-DTG curve of the catalyst prepared in Example 1;
[0032] Figure 3 The effect of reaction temperature on product molecular weight and conversion rate in Example 7;
[0033] Figure 4 The effect of reaction pressure on product molecular weight and conversion rate in Example 8;
[0034] Figure 5 The effect of feed ratio on product molecular weight and conversion rate in Example 9;
[0035] Figure 6 The effect of the single monomer input amount on the product molecular weight and conversion rate in Example 10;
[0036] Figure 7 The effect of the number of times the catalyst is reused on the product molecular weight and conversion rate of Example 11;
[0037] Figure 8 The present invention is a schematic structural diagram of an external circulation kettle reactor for synthesizing high molecular weight polypropylene glycol. DETAILED DESCRIPTION
[0038] The present invention is described in further detail below.
[0039] Example 1
[0040] A supported multi-metal cyanide complex catalyst, the molecular formula of which is: Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn[Ni(CN)4]@MCM-41(OH-)·ZnCl2·La(NO3)3· t BuOH·Igepal CA-520, the preparation method thereof comprises the following steps:
[0041] (1) MCM-41 powder with Si / Al (m / m) = 25 was placed in a muffle furnace and calcined at a calcination temperature of 550°C in an air atmosphere for 5 hours. The calcined MCM-41 molecular sieve was mixed with 0.10 mol / L NaOH solution at a solid-liquid ratio (g / mL) of 1:20 in a round-bottom flask, stirred at 65°C at a stirring rate of 800 rpm for 0.5 hours, then the round-bottom flask was cooled to room temperature, washed with water and filtered to pH = 7, dried at 110°C for 10 hours, and the obtained solid was ground into powder; then the powder was added to 0.5 mol / L NH4Cl solution at a solid-liquid ratio (g / mL) of 1:20, ion exchange was performed at 60°C for 1 hour and filtered, the above operation was repeated four times, and then washed with deionized water until the filtrate did not contain chloride ions, and dried in an oven at 110°C overnight to obtain an alkali-treated MCM-41 carrier, which was recorded as MCM-41 (OH-);
[0042] (2) Prepare four solutions: 1.0 g K3[Co(CN)6], 0.1 g K3[Fe(CN)6], and 0.1 g K2[Ni(CN)4] were dissolved in 10 ml of deionized water to prepare three metal cyanide aqueous solutions, named solution A, solution B, and solution C respectively; 1 g alkali-treated MCM-41(OH - ) was dispersed in 10 ml of deionized water, and then 4.0 g of ZnCl2, 0.1 g of La(NO3)3, and 15 ml t BuOH and 5.0 g Igepal CA-520 to prepare solution D.
[0043] (3) At 80° C. and 3000 rpm, solution A, solution B, and solution C were simultaneously added dropwise to solution D within 20 min, and stirring was continued for 1 h to obtain a catalyst slurry.
[0044] (4) Filter the catalyst slurry five times with deionized water: After the first filtration, use 100 ml of t The mixed solution of BuOH and water is slurried, wherein t The volume ratio of BuOH to water is 1:2; after pulping, filter for the second time, and use 100ml of t The mixed solution of BuOH and water is slurried, whereint The volume ratio of BuOH to water is 1:1; after pulping, filter for the third time, and use 100ml of t The mixed solution of BuOH and water is slurried, wherein t The volume ratio of BuOH to water is 2:1; after pulping, the fourth filtration is performed, and after filtration, 100 ml of t BuOH was used for pulping; after pulping, the fifth filtration was performed, and after filtration, the filter cake was placed in a vacuum drying oven and dried overnight at 65°C to obtain a supported multi-metal cyanide complex catalyst: MCM-41(OH-)@Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn[Ni(CN)4]·ZnCl2·La(NO3)3· t BuOH Igepal CA-520.
[0045] Figure 1 This is a SEM image of the catalyst prepared in Example 1, wherein Figure 1 Figure a is the overall SEM image. Figure 1 Figure b is a local SEM image, which shows that the carrier and the active component are well combined. The pore size of the MCM-41 molecular sieve carrier modified by alkali is enlarged, exposing more active sites, and multi-metal cyanide complex catalyst grows on it. The prepared MMC has a distinct lamellar structure, such as Figure 1 b in the figure, and the flake MMCs aggregate together in a relatively stable environment to form a certain cluster structure.
[0046] Figure 2 The TG-DTG curve of the catalyst prepared in Example 1 is used to determine the binding state of the ligands, co-complexing agents and the main framework of the catalyst zinc hexacyanocobaltate by thermal analysis. The supported MMC catalyst complexes two organic ligands, small molecule organic matter and high molecular polymer, and its composition and structure are more complex than the zinc hexacyanocobaltate sample. Its TG curve is also more complex, and there is no obvious step on the curve, indicating that the boundaries between the decomposition stages are not very clear and the complexity of the ligand binding state. The mass loss can be roughly divided into three stages. The first is the rapid removal of physically adsorbed water, followed by the removal of free organic ligands and co-complexing agents, and finally the removal of cyanide ligands.
[0047] Comparative Example 1
[0048] A supported double metal cyanide complex catalyst, which differs from Example 1 only in that Zn3[Fe(CN)6]2 and Zn[Ni(CN)4] are not added, and its structural formula is: Zn3[Co(CN)6]2@MCM-41(OH-)·ZnCl2·La(NO3)3· t BuOH Igepal CA-520.
[0049] Comparative Example 2
[0050] A supported multi-metal cyanide complex catalyst, which differs from Example 1 only in that Zn[Ni(CN)4] is not added, and has the structural formula: Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2@MCM-41(OH-)·ZnCl2·La(NO3)3· t BuOH Igepal CA-520.
[0051] Comparative Example 3
[0052] A supported multi-metal cyanide complex catalyst, which differs from Example 1 only in that Zn3[Fe(CN)6]2 is not added, and has the structural formula: Zn3[Co(CN)6]2·Zn[Ni(CN)4]@MCM-41(OH-)·ZnCl2·La(NO3)3· t BuOH Igepal CA-520.
[0053] Comparative Example 4
[0054] A supported multi-metal cyanide complex catalyst, which differs from Example 1 only in that Zn3[Fe(CN)6]2 and Zn[Ni(CN)4] are not added, and K4Fe(CN)6 is added, and its structural formula is: Zn3[Co(CN)6]2·K4Fe(CN)6@MCM-41(OH-)·ZnCl2·La(NO3)3· t Preparation method of BuOH·Igepal CA-520.
[0055] Comparative Example 5
[0056] A supported multi-metal cyanide complex catalyst, which differs from Example 1 only in that Ige palCA-520 is not added, and has the structural formula: Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn[Ni(CN)4]@MCM-41(OH-)·ZnCl2·La(NO3)3· t BuOH.
[0057] Catalyst performance testing:
[0058] The catalyst performance test was carried out on the catalysts in Example 1 and Comparative Examples 1-5, and they were used to catalyze the polymerization of small molecule polypropylene glycol and propylene oxide to generate high molecular weight polypropylene glycol in an external circulation kettle reactor, and the synthetic target molecular weight was 3000. The specific test conditions were as follows: the reaction starting pressure was 0.2Mpa, and the reaction temperature was 120°C; the total feed amount of the initiator PPG-400 was 8g, which was added at one time; the total feed amount of propylene oxide was 52g, and the single feed amount of propylene oxide was 3g, which was added in small amounts multiple times. After the reaction, the product was collected, and the unreacted monomer was separated by vacuum rotary evaporation to obtain a high molecular weight polypropylene glycol product, and the hydroxyl value of the high molecular weight polypropylene glycol product was titrated by phthalic anhydride method. The results are shown in Table 1.
[0059] Table 1 Comparison of catalyst performance tests of Example 1 and Comparative Examples 1-5
[0060]
[0061] It can be seen from Table 1 that under the same reaction time, the catalytic performance of Example 1 is greatly improved compared with that of Comparative Examples 1-5, which can be attributed to two reasons: first, the elements Ni(II), Fe(III), and Fe(II) added in Example 1 reduce the crystallinity of the MMC catalyst and increase the specific surface area of the catalyst; second, the co-complexing agent Igepal CA-520 added in Example 1 realizes the control of the particle size of the MMC catalyst, synthesizes a nanoscale catalyst, and reacts with the active components of ZnCl2, Zn3[Co(CN)6]2, Zn3[Fe(CN)6]2, Zn[Ni(CN)4] and K4Fe(CN)6, which promotes the coordination of Zn with oxygen in IgepalCA-520 and generates new active sites. The above two reasons enhance the catalytic activity of the catalyst.
[0062] In addition, metal Ni(Ⅱ), Fe(Ⅲ) and Fe(Ⅱ) all have the strongest catalytic activity. The single metal catalytic effect of Ni(Ⅱ) is better than that of Fe(Ⅲ) and Fe(Ⅱ), and Ni(Ⅱ) and Fe(Ⅲ) have a synergistic effect in this reaction. This may be due to the fact that Ni 2 + , Fe 3+ High specific capacitance and Co 2+ The synergistic effect between the redox-rich valence states of the ions improves the structural stability of the four-coordinated nanosheets, thereby promoting the activation of active centers.
[0063] Example 2
[0064] Two groups of parallel experiments were designed. The specific preparation method was the same as that in Example 1, the differences were as follows: in one group, the amount of K2[Ni(CN)4] added in step (2) was different, and the amounts of K2[Ni(CN)4] added were 0.05 g, 0.10 g and 0.15 g, respectively; in the other group, the amount of K3[Fe(CN)6] added in step (2) was different, and the amounts of K3[Fe(CN)6] added were 0.05 g, 0.10 g and 0.15 g, respectively.
[0065] The catalyst performance was tested for catalysts with different addition amounts of nickel potassium cyanide and potassium ferrocyanide, and the product was titrated for hydroxyl value. The results are shown in Table 2-1 and Table 2-2 respectively.
[0066] Table 2-1 Performance test comparison of catalysts with different nickel potassium cyanide addition amounts
[0067]
[0068] Table 2-2 Performance test comparison of catalysts with different potassium ferrocyanide addition amounts
[0069]
[0070] It can be seen from Table 2-1 and Table 2-2 that with the increase of potassium nickel cyanide and potassium ferrocyanide, the catalytic performance of the catalyst shows a trend of first increasing and then decreasing under the same reaction time. This is because the introduction of elements Ni (II) and Fe (III) can improve the activity of the catalyst, but when the elements Ni (II) and Fe (III) are too much, although the crystallinity of MMC is further reduced, it also blocks the active center of MMC, so its induction period is relatively longer and the reaction rate is slower.
[0071] Example 3
[0072] Four parallel experiments were designed, and the specific preparation method was the same as in Example 1, except that the amount of ZnCl2 added in step (2) was different, and the addition amount was 2.0g, 4.0g, 6.0g, 8.0g and 10.0g respectively. The catalyst performance of the catalyst synthesized by different ZnCl2 addition amounts was tested, and the product was titrated for hydroxyl value, and the results are shown in Table 3.
[0073] Table 3 Performance test table of the catalyst synthesized by different ZnCl2 addition amounts
[0074]
[0075] It can be seen from Table 3 that too much or too little ZnCl2 addition will affect the performance of the catalyst. When the ZnCl2 addition amount is 4.0g, the catalytic performance of the synthesized catalyst is the best.
[0076] Example 4
[0077] Three groups of parallel experiments were designed. The specific preparation method was the same as that in Example 1, except that the carriers in step (1) were different. The carriers were MCM-41 with Si / Al (m / m) = 25, Hβ with Si / Al (m / m) = 25, ZSM-5 with Si / Al (m / m) = 70, and SiO2 with Si / Al (m / m) = 25.
[0078] The catalyst performance tests were carried out on the catalysts loaded on different carriers, and the hydroxyl value titration was performed on the products. The results are shown in Table 4.
[0079] Table 4 Performance test table of catalysts with different carriers
[0080]
[0081] It can be seen from Table 4 that when MCM-41 (Si / Al=25) is used as a carrier, the synthesized catalyst has the best catalytic performance. This is because MCM-41 (Si / Al=25) has unique acidity and pore structure, which can provide more active sites.
[0082] Example 5
[0083] Four groups of parallel experiments were designed. The specific preparation method was the same as that in Example 1, except that in step (1), whether NaOH solution was used and different NaOH solution concentrations were used for alkali treatment, namely, no NaOH solution was used and the NaOH solution concentrations were 0.05 mol / L, 0.10 mol / L, 0.15 mol / L and 0.20 mol / L respectively.
[0084] The catalyst performance of the catalyst prepared by treating the carrier with different NaOH solution concentrations was tested, and the hydroxyl value of the product was titrated. The results are shown in Table 5.
[0085] Table 5 Catalyst performance test table of different NaOH solution concentrations
[0086]
[0087] As shown in Table 5, the catalyst prepared when the concentration of NaOH solution is 0.10 mol / L has the best catalytic effect. This is because the appropriate alkali treatment concentration further increases the pore volume and specific surface area of the carrier MCM-41 (Si / Al=25), and the number of active sites increases. However, too low alkali treatment concentration has no obvious effect, and too high alkali treatment concentration will destroy the pore structure of the molecular sieve, causing pore collapse and a reduction in active sites.
[0088] Example 6
[0089] Three groups of parallel experiments were designed. The specific preparation method was the same as that in Example 1, except that the co-complexing agents in step (2) were different, namely Igepal CA-520, PPG-3000, PTMEG and P123.
[0090] The catalyst performance of the catalysts with different co-complexing agents was tested, and the hydroxyl value of the product was titrated. The results are shown in Table 6.
[0091] Table 6 Catalyst performance test table with different co-complexing agents
[0092]
[0093] Without the addition of a co-complexing agent, the performance of the MMC catalyst is low, so it is necessary to add a suitable co-complexing agent to complex with the MMC catalyst to activate their activity in propylene oxide polymerization. It can be seen from Table 6 that compared with polymer PPG-3000, polytetramethylene ether glycol (PTMEG) and triblock polymer P123, Igepal CA-520 has a more significant effect in improving catalyst stability and dispersibility. This may be due to the co-condensation of ammonia-catalyzed MCM-41 (OH-) particles in the reverse microemulsion of Igepal CA-520, resulting in a partially condensed nanosphere system, which promotes the dispersion of the MMC catalyst, forms a smaller nano-scale MMC, and increases the surface area of the catalyst.
[0094] Example 7
[0095] The catalyst and reaction raw materials prepared in Example 1 were used to synthesize high molecular weight polypropylene glycol. Four sets of parallel experiments were designed to investigate the effect of reaction temperature on the synthesis of high molecular weight polypropylene glycol. The reaction temperatures were set at 100°C, 110°C, 120°C, 130°C, and 140°C, respectively. The results are shown in Table 1. Figure 3 .
[0096] Depend on Figure 3 It can be seen that the conversion rate of propylene oxide and the molecular weight of the product first increase and then stabilize with the increase of reaction temperature. As the temperature increases, the rate of polymerization reaction is significantly accelerated, but when the temperature reaches 120°C, the catalyst performance tends to be stable, but further increasing the temperature will lead to more product by-products, darker product color, and increased additional energy consumption. It can be seen that the reaction temperature required for the prepared supported MMC catalyst is lower than that of the current MMC catalyst, which improves operational safety and reduces energy consumption.
[0097] Example 8
[0098] Four sets of parallel experiments were designed. The difference from Example 6 is that the pressures of the synthesis polymer polypropylene glycol reaction were different, and were set to 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, and 0.5 MPa, respectively. The results are shown in Table 1. Figure 4 .
[0099] The reaction pressure affects the solubility of propylene oxide in the liquid phase. Within a certain range, the greater the pressure, the greater the solubility. The greater the solubility, the greater the probability of effective collision between propylene oxide, glycerol and the catalyst. Pressurization increases the equilibrium constant of the polymerization reaction and causes the reaction to proceed in the positive direction (the direction in which the number of gas molecules decreases). Figure 4 It can be seen that the conversion rate of propylene oxide and the molecular weight of high molecular weight polypropylene glycol do not change much with pressure: when the pressure reaches 0.2Mpa, the reaction results gradually stabilize.
[0100] Example 9
[0101] Four sets of parallel experiments were designed. The difference from Example 6 was that the material ratios of the initiator and propylene oxide in the reaction for synthesizing high molecular weight polypropylene glycol were different, namely 8g:12g, 8g:32g, 8g:52g, 8g:62g, and 8g:72g, respectively. The target molecular weights of the synthesized high molecular weight polypropylene glycol were 1000, 2000, 3000, 3500, and 4000, respectively. The results are shown in Table 1. Figure 5 .
[0102] Depend on Figure 5 It can be seen that with the increase of the target molecular weight of the synthesized high molecular weight polypropylene glycol, the conversion rate also continues to increase, indicating that the catalyst has a good application prospect in the synthesis of high molecular weight polypropylene glycol.
[0103] Example 10
[0104] Four parallel experiments were designed. The difference from Example 6 is that when the initiator dosage is constant, the single dosage of propylene oxide is different. The total dosage of initiator PPG-400 is 8g, which is added at one time; the total dosage of propylene oxide is 52g, and the single dosage of propylene oxide is set to 1g, 3g, 6g, 9g, and 12g respectively, which is added in small amounts and multiple times. The results are shown in Figure 6 .
[0105] Depend on Figure 6 It can be seen that when the total amount of propylene oxide is constant, the single amount of propylene oxide has a particularly significant effect on the distribution width of the high molecular weight polypropylene glycol product. The smaller the single amount, the narrower the distribution width, the better the polymerization effect, and the higher the product quality.
[0106] Embodiment 11
[0107] After the reaction of Example 1, the solid catalyst was filtered out and washed repeatedly with tert-butyl alcohol and water to remove the residual small molecular weight polypropylene glycol product adhering to the catalyst surface. The recovered catalyst was vacuum dried and then used in the synthesis experiment. The obtained catalyst was used again in the reaction to test the life and renewability of its catalytic activity. This process was repeated 5 times to obtain 6 groups of performance comparisons. The results are shown in Figure 7 .
[0108] Depend on Figure 7 It can be seen that the conversion rate of the catalyst is still maintained above 94.5% after being recycled for 5 times, indicating that the prepared supported MMC catalyst has high stability, the active ingredients are not easily lost, and the reusability is good, so it has good prospects for industrial application.
[0109] Example 12
[0110] like Figure 8 As shown, the present invention provides an external circulation autoclave reactor for synthesizing high molecular weight polypropylene glycol, comprising an autoclave body, an autoclave controller 18, an external circulation system and an air intake system. The autoclave body is provided with a stirring device and a heating device for heating the autoclave.
[0111] The reactor body of this embodiment includes a reactor body fixed on a bracket, the reactor body is provided with a reactor cover component, the reactor cover component includes a cover body, the stirring device is a strong magnetic coupling stirrer 5 fixed on the cover body, and a thermometer 4 is also fixed on the cover body; the thermometer 4 is inserted into the interior of the reactor body; the strong magnetic coupling stirrer 5 is connected to the servo speed regulating motor 1 through a transmission belt 3. The strong magnetic coupling stirrer 5 includes a stirring paddle 9 extending into the reactor body, and a cooling coil 8 is provided on the stirring paddle 9, and the cooling coil 8 is connected to a condensing water pipe (not shown in the figure). The reactor body is provided with a high-temperature and high-pressure needle valve 6 for controlling the pressure in the reactor body and a pressure gauge 7 for detecting the pressure of the reactor body. The heating device includes a heating layer 10 arranged on the inner side wall of the reactor body, an insulation layer 11 is provided on the outer side wall of the reactor body, and a mesh screen 12 for filtering the catalyst is provided in the reactor body. The autoclave controller 18 is electrically connected to the heating layer 10 and the servo speed regulating motor 1 respectively, and the autoclave controller 18 can control the temperature and stirring rate in the reactor.
[0112] The air intake system of this embodiment includes a nitrogen cylinder 20 and a propylene oxide cylinder 21. An air intake pipeline is connected between the nitrogen cylinder 20 and the propylene oxide cylinder 21 and the kettle body, and a gas three-way valve 19 is provided on the air intake pipeline.
[0113] The external circulation system of this embodiment includes an external circulation outlet 13 located at the lower part of the reactor body, a pump inlet pipeline 14 connected to the external circulation outlet 13, a plunger pump 15 connected to the pump inlet pipeline 14, the plunger pump 15 is connected to a pump outlet pipeline 16, and the pump outlet pipeline 16 is provided with an external circulation inlet 17 located at the upper part of the reactor body. All pipelines and pump internal fittings are made of 316L stainless steel.
[0114] Working process: Add materials and catalysts into the kettle to carry out the synthesis reaction of high molecular weight polypropylene glycol. The materials in the kettle are filtered by the catalyst screen and flow out from the external circulation outlet 13, and flow into the plunger pump 15 through the pump inlet pipeline 14. The plunger pump 15 then transports the materials through the pump outlet pipeline 16 to the external circulation inlet 17, and flows back into the kettle to form an external circulation reaction.
Claims
1. A supported multi-metal cyanide complex catalyst, characterized in that: The catalyst satisfies the following general formula: Zn3[Co(CN)6]2·Zn3[Fe(CN)6]2·Zn[Ni(CN)4]@MCM-41(OH-)·vZnCl2·xLa(NO3)3·y t BuOH·z Igepal CA-520, wherein MCM-41(OH-) represents an alkali-treated mesoporous molecular sieve; v=0.5-3, x=0-0.01, y=0.1-2, z=0-0.
1.
2. A method for preparing the supported multi-metal cyanide complex catalyst according to claim 1, characterized in that: The following steps are involved: (1) calcining MCM-41 powder and mixing it with alkali solution, stirring, cooling to room temperature, washing, drying, and grinding the product into powder; adding the powder into an ion exchange solution for ion exchange, washing, filtering, and drying to obtain an alkali-treated MCM-41 carrier, which is recorded as MCM-41(OH-); (2) Dissolve three metal cyanides, K3[Co(CN)6], K3[Fe(CN)6] and K2[Ni(CN)4], respectively. The resulting solutions are named solution A, solution B and solution C. MCM-41(OH - ) was dispersed in a solvent to obtain MCM-41(OH - ) solution, then add ZnCl2, La(NO3)3, t BuOH and Igepal CA-520, and the resulting solution was named solution D; (3) adding solution A, solution B and solution C dropwise to solution D, stirring, to obtain a catalyst slurry; The catalyst slurry is filtered, washed and dried to obtain the supported multi-metal cyanide complex catalyst.
3. The method for preparing a supported multi-metal cyanide complex catalyst according to claim 2, characterized in that: In step (2), the concentration of K3[Co(CN)6] solution is 0.05-0.5 g / ml, and the concentrations of K3[Fe(CN)6] and K2[Ni(CN)4] solutions are 5-20% of the concentration of K3[Co(CN)6] solution, respectively.
4. The method for preparing a supported multi-metal cyanide complex catalyst according to claim 2, characterized in that: In step (2), the t The mass ratio of BuOH to MCM-41(OH-) solution is 1:1-2, the mass ratio of ZnCl2 to MCM-41(OH-) is 5-1:1, and the mass ratio of the sum of the masses of the three metal cyanides to MCM-41(OH-) is 2-1:
1.
5. The method for preparing a supported multi-metal cyanide complex catalyst according to claim 2, characterized in that: In step (2), the mass ratio of La(NO3)3 to MCM-41(OH-) is 1:5-20; the mass ratio of Igepal CA-520 to MCM-41(OH-) is 2-1:
1.
6. Use of the supported multi-metal cyanide complex catalyst according to claim 1 in the preparation of high molecular weight polypropylene glycol.
7. Use of the supported multi-metal cyanide complex catalyst according to claim 6 in the preparation of high molecular weight polypropylene glycol, characterized in that: The reaction temperature is 100-140°C and the pressure is 0.1-0.5MPa.
8. Use of the supported multi-metal cyanide complex catalyst according to claim 6 in the preparation of high molecular weight polypropylene glycol, characterized in that: The feed ratio is 8:12-72.
9. Use of the supported multi-metal cyanide complex catalyst according to claim 6 in the preparation of high molecular weight polypropylene glycol, characterized in that: The device used for synthesizing high molecular weight polypropylene glycol is an external circulation autoclave reactor; the external circulation autoclave reactor comprises an autoclave body, an air intake system and an external circulation system; the autoclave body is provided with a stirring device and a heating device for heating the autoclave, the stirring device and the heating device are respectively connected to a high pressure autoclave controller (18); the air intake system is connected to the autoclave body for conveying raw material gas and protective gas to the autoclave body; the external circulation system comprises a plunger pump (15), the plunger pump (15) is respectively connected to an external circulation outlet (13) at the bottom of the autoclave body and an external circulation inlet (17) at the top of the autoclave body through pipelines.
Citation Information
Patent Citations
Double-metal cyanide complex catalyst, preparation method thereof and preparation method of polypropylene glycol
CN112250856A
Supported metal cyanide complex catalyst as well as preparation method and application thereof
CN113881032A
Supported multi-metal cyanide complex catalyst as well as preparation method and application thereof
CN115260479A
Preparation and application of nonmetal modified monatomic catalyst for preparing ethanol through CO2 hydrogenation
CN117181260A
Acid-base bifunctional catalyst for catalyzing dimethyl carbonate and ethanol to synthesize methyl ethyl carbonate
CN118022713A